Multi-scale phenomena in complex fluids : modeling, analysis and numerical simulation - Hou, Thomas Y.; Liu, Chun; Liu, Jian-Guo (Series in contemporary applied mathematics ;, 2009)
Multi-Scale Phenomena in Complex Fluids is a collection of lecture notes delivered during the first two series of mini-courses from "Shanghai Summer School on Analysis and Numerics in Modern Sciences", which was held in 2004 and 2006 at Fudan University, Shanghai, China. This review volume of 5 chapters, covering various fields in complex fluids, places emphasis on multi-scale modeling, analyses and simulations. It will be of special interest to researchers and graduate students who want to work in the field of complex fluids